Distribution of Deroceras reticulatum (Müller, 1774) (Pulmonata stylommatophora) in Argentina with first record of the Reserva de Usos Múltiples Isla Martin Garcia, Río de la Plata superior - Martin, Stella Maris (2009)
Deroceras reticulatum is a misanthropic European species spread widely throughout South America. At the moment this species is considered a 'pest' in direct sowing such as maize, soybean, sunflower, wheat, alfalfa and clovers, among others. The aim of this paper is to report the first record of D. reticulatum in the Reserva de Usos Multiples Isla Martín García, Buenos Aires province and to provide information about this species distribution in five Argentina provinces.